1998
DOI: 10.1021/bi981325j
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Synthase Mutations That Alter Cofactor Chemistry Lead to Mechanism-Based Inactivation

Abstract: Mutations in the pyridoxal phosphate binding site of the tryptophan synthase beta subunit (S377D and S377E) alter cofactor chemistry [Jhee, K.-H., et al. (1998) J. Biol. Chem. 273, 11417-11422]. We now report that the S377D, S377E, and S377A beta2 subunits form alpha2 beta2 complexes with the alpha subunit and activate the alpha subunit-catalyzed cleavage of indole 3-glycerol phosphate. The apparent Kd for dissociation of the alpha and beta subunits is unaffected by the S377A mutation but is increased up to 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 59 publications
(109 reference statements)
4
20
0
Order By: Relevance
“…In this class of PLP enzymes, a polar residue (serine or threonine) is always found within hydrogen-bonding distance to the pyridinium nitrogen, either close to the back (si face) or the front (re face) of the cofactor, except in aminocyclopropane deaminase, where a glutamate is found directly below the PLP (27). Threonine synthase departs from this trend as a histidine is located on the re face.…”
Section: Resultsmentioning
confidence: 99%
“…In this class of PLP enzymes, a polar residue (serine or threonine) is always found within hydrogen-bonding distance to the pyridinium nitrogen, either close to the back (si face) or the front (re face) of the cofactor, except in aminocyclopropane deaminase, where a glutamate is found directly below the PLP (27). Threonine synthase departs from this trend as a histidine is located on the re face.…”
Section: Resultsmentioning
confidence: 99%
“…The charge density of the pyridine ring is strictly modulated by various factors in the neighborhood of the pyridine nitrogen atom in the PLP enzyme. [18][19][20][21] The pyridine nitrogen atom of hACCD exists within hydrogen bond distance (2.5 Å ) of the side-chain carboxyl oxygen atom of Glu296, which is not the case for other members of the TRPSb family. The crystallographically analyzed enzymes of this family are TRPSb, 22 O-acetylserine sulfhydrylase (cysteine synthase), 23 threonine deaminase, 24 threonine synthase, 25 and cystathionine b-synthase.…”
Section: Insight Into Inertnessmentioning
confidence: 90%
“…There was no significant change in the catalytic activity with DL-DAP as substrate (Table 1) with both mutant enzymes, as observed in the case of OASS [19]. Mutation of the corresponding residue in the enzymes which follow the E 1 CB mechanism of b-elimination (TrpS and CBS) resulted in complete loss of activity [20,21]. These results suggested that the residue hydrogen bonded to the pyridine nitrogen is not crucial for b-elimination activity by DAPAL and might follow the anti-E 2 mechanism, as proposed for OASS [19].…”
Section: Discussionmentioning
confidence: 70%
“…). Such a pH‐dependent change in the absorbance spectrum was observed with the S377D mutant of TrpS β‐subunit which follows the E 1 CB mechanism . Mutation of Ser289 in yeast CBS to Ala or Asp resulted in a drastic reduction in β‐replacement activity and the fluorescence resonance energy transfer between the tryptophan residues of the enzyme and PLP was diminished or absent in the mutants, demonstrating that the Ser289 was essential for maintaining proper orientation of PLP.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation